2019
DOI: 10.1103/physrevc.100.034601
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the B10(α,n0)13N cross section

Abstract: The National Ignition Facility provides the opportunity to study nuclear reactions under controlled conditions at high temperatures and pressures at a level never before achieved. However, the time scale of the deuterium-tritium (DT) implosion is only a few nanoseconds, making data collection and diagnostics very challenging. One method that has been proposed for obtaining additional information about the conditions of the implosion is to activate a dopant material using the αparticles produced from the DT fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Further, as is shown below, the main contributors to the reaction rate are from the previously observed strong resonance at E α = 1.51 MeV and from the newly proposed strong low energy resonance. Angular distribution measurements are available from Van der Zwan and Geiger [13] and Liu et al [46] for this resonance and they are in good agreement with R-matrix fit as shown in Fig. 11.…”
Section: Reaction Ratesupporting
confidence: 66%
See 3 more Smart Citations
“…Further, as is shown below, the main contributors to the reaction rate are from the previously observed strong resonance at E α = 1.51 MeV and from the newly proposed strong low energy resonance. Angular distribution measurements are available from Van der Zwan and Geiger [13] and Liu et al [46] for this resonance and they are in good agreement with R-matrix fit as shown in Fig. 11.…”
Section: Reaction Ratesupporting
confidence: 66%
“…Alpha particle energies are in units of MeV, cross sections are in b/sr. Cross sections are from the present work except those at Eα = 1.5 MeV, which were measured as part of the experiment reported in Liu et al [46]. The data have common systematic uncertainty of 12% as discussed in Sec.…”
Section: R-matrix Analysismentioning
confidence: 90%
See 2 more Smart Citations